Phenomenon-based learning in Finland - Naik, Rajani Prakash (2019)
The purpose of this study is to understand Finnish teachers’ teacher trainers’ and school leaders’ perspectives on Phenomenon-Based Learning (PhBL) and its implementation as a pedagogical approach. In order to best inform future practices and borrowing within and from the Finnish education system, it is important to represent the practitioners’ voice in the discourse around PhBL. This study was conducted with two secondary school teachers, a teacher trainer and a school leader from two different municipalities in Finland. The data collection process involved detailed semi-structured interviews in order to uncover perceptions, reflections and opinions regarding the implementation of PhBL in Finnish primary and secondary grade classrooms. This data was analysed through the methods of thematic analysis. The result of this study shows that PhBL is perceived in two manners - one as removing unnatural and inorganic silos in education such as subjects and the other as learning being driven and directed by the learner. Further themes emerged which discussed the challenges and support systems that exist in implementing PhBL and addressed the changing world and its mandates for education. This research project concluded that although Finland is making headway in addressing the needs of the changing world through education, a significant amount of support and motivation is required to make further progress.